Students’ Needs for Virtual Reality-Based Arabic Language Learning Through Hikayat Sya’biyah - Kinanthi, Keysha Wahyu; Kholisin; Fauzi, Moh. Fery; Ikhsan, M. Alifudin; Ziafia, Roby Kavin Ahmad Fawwaz; Guangli, Mi (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2026)
The transformation of Arabic language learning in the digital era requires not only relevant content but also interactive, immersive, and cognitively engaging learning experiences. However, conventional instruction remains text-centered and limits contextual and affective engagement. This study aimed to identify students’ pedagogical needs and construct an evidence-based framework for immersive Arabic learning through Virtual Reality (VR) and Hikayat Sya’biyah. Using a quantitative descriptive design, data were collected from 128 university students through a Likert-scale questionnaire and analyzed using percentage statistics. The findings revealed that students prioritized instructional media (90%) and immersive technology (93%), exceeding learning challenges (65%), affective needs (79%), and cultural integration (87%). These findings indicate that students primarily seek experiential and affective learning environments, while cultural content becomes pedagogically meaningful when embedded within immersive interaction. Accordingly, this study proposes a four-layer framework consisting of psychological readiness, immersive exploration, situated interaction, and cultural internalization.